Diagnóstico das condições de saneamento básico da microrregião de Cametá-PA - GAIA, Franciana Valente (2023)
The current scenario of basic sanitation in the North Region raises concerns, especially in the micro-region of Cametá, so the interest in carrying out this study arose, by verifying the existence of few researches carried out on basic sanitation in the micro-region of Cametá and substantially considering that there is the structuring of the basic sanitation system, in this way, this work tried to talk about the diagnosis of the basic sanitation conditions of the microregion of Cametá - PA, in order to evaluate the basic sanitation conditions of the municipalities that make up the micro-region of Cametá-Pará. Therefore, it was necessary to describe the basic sanitation conditions based on the selection of some sectorial indicators, identify the existence of sanitation policies and plans in the municipalities studied and prepare thematic maps that illustrate the basic sanitation conditions of the municipalities of the microregion of Cametá. The method used was based on a basic research with a qualitativequantitative and exploratory approach. In view of this, it was found that there are no basic sanitation policies and plans in most municipalities, as well as some of the basic sanitation services are not satisfactory and the absence of collection and treatment of sanitary sewage and urban drainage infrastructure, where it was possible to conclude that the micro-region presents a great delay in the universalization of basic sanitation services.